2013
DOI: 10.3390/medicina49120084
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the First Successful Heart-Lung Transplantation in the Baltic Countries

Abstract: Successful heart-lung complex transplantation was performed in a 48-year-old man. During the postoperative period, M. tuberculosis infection was diagnosed, and the treatment subsequently started. One year after, the patient was urgently hospitalized due to myocardial infarction. However, despite the best efforts, the patient died. Antituberculosis treatment is recommended to all the patients with confirmed active tuberculosis. Treatment of tuberculosis in transplant recipients is similar to that of the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%